2013
DOI: 10.1002/ange.201300871
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzopentalenes from B(C6F5)3‐Induced Cyclization Reactions of 1,2‐Bis(phenylethynyl)benzenes

Abstract: 'Lene' and mean: The strong Lewis acid B(C6F5)3 efficiently converts some bis(arylethynyl)benzenes into dibenzopentalenes through a series of Lewis acid induced cyclization reactions at room temperature. Thus the reaction has the potential to be useful in the synthesis of substituted dibenzopentalene derivatives which are difficult to make by conventional means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In recent years, dibenzopentalene derivatives have attracted considerable attentions because of their unique planar structures, antiaromatic characters and promising application in organic materials science 20,21 . Several reliable methods for the synthesis of dibenzopentalene derivatives were designed and reported [22][23][24][25][26][27][28][29][30] . In case of dinaphthopentalene derivatives, Kawase et al 31 reported the unique synthesis and application in organic thinfilm transistors.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, dibenzopentalene derivatives have attracted considerable attentions because of their unique planar structures, antiaromatic characters and promising application in organic materials science 20,21 . Several reliable methods for the synthesis of dibenzopentalene derivatives were designed and reported [22][23][24][25][26][27][28][29][30] . In case of dinaphthopentalene derivatives, Kawase et al 31 reported the unique synthesis and application in organic thinfilm transistors.…”
Section: Resultsmentioning
confidence: 99%
“…In these early cases, 1,1‐carboboration reactions were observed whereby a 1,2‐alkyl/aryl shift occurs between the distal and proximal carbons of the alkyne with the concomitant 1,2‐shift of the R group from boron to carbon (Scheme , top). Further to this, Erker has demonstrated extensive use of the carboboration mechanism to affect a number of complex rearrangement processes such as benzannulations and cyclizations, amongst others …”
Section: Methodsmentioning
confidence: 99%
“… Unsymmetrical benzo‐ ( 25 ) and dibenzopentalene derivatives ( 27 ) according to Diederich et al 12. and Erker et al 13…”
Section: Methodsmentioning
confidence: 99%
“…Unsymmetrical dibenzopentalenes have been synthesized in another single‐step transformation recently reported by Erker, Yamaguchi, and co‐workers 13. In this case 1,2‐bis(phenylethynyl)benzenes were employed as substrates and isomerized by an intramolecular cyclization using the strong Lewis acid B(C 6 F 5 ) 3 as shown in Scheme for the tetrafluoro derivative 26 .…”
Section: Methodsmentioning
confidence: 99%